Multiinfarct dementia vs Alzheimer's disease: sonographic criteria - Biedert, Stefan; Förstl, Hans; Hewer, Walter (Angiology, 1995)
Primary degenerative dementia of the Alzheimer type (DAT) and multiinfarct dementia (MID) exhibit differences in cerebrovascular blood flow velocity profiles, which were investigated by means of transcranial Doppler sonography The pulsatility indices, as angle-independent parameters of peripheral vascular resistance, measured in middle cerebral and basilar arteries of patients with MID, were significantly increased (P < 0.005) with respect to cases of primary DAT and to healthy age-matched controls. Approximately 75% of all MID patients exhibited small-vessel disease rather than throm boembolism from the extracranial arteries and the heart, as judged by extracranial and transcranial Doppler sonographies, computerized cerebral tomographies, EEGs, and, if necessary, 2-D echocardiographies.